2019
DOI: 10.33411/ijist/2019010101
|View full text |Cite
|
Sign up to set email alerts
|

Appraisal of Urban Heat Island over Gujranwala and its Environmental Impact Assessment using Satellite Imagery (1995-2016).

Abstract: Rapid urbanization and concretization are the main sources of formation and existence of Urban Heat Island (UHI). Due to high concentration of pollutants in urban environments, the residents are exposed to unexpected health issues. This study aims at delineating the temporal variations in the spatial extent of UHI over Gujranwala using Landsat thermal imagery. It also aims at determining the variations in pollutant concentration in the atmosphere due to vehicle's tailpipe emissions and fossil fuel burning by i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 27 publications
0
14
0
Order By: Relevance
“…Spatial interpolation is widely used in trend mapping e.g., the weather experts use interpolation to construct weather maps to determine temporal variations in rainfall, temperature, humidity or pressure for a specific time span [17]. There are basic three types of spatial interpolations that include Inverse Distance Weightage (IDW), Kriging and Spline [18]. We can accept or reject any of the technique depending upon the application for which we are applying it.…”
Section: Methodsmentioning
confidence: 99%
“…Spatial interpolation is widely used in trend mapping e.g., the weather experts use interpolation to construct weather maps to determine temporal variations in rainfall, temperature, humidity or pressure for a specific time span [17]. There are basic three types of spatial interpolations that include Inverse Distance Weightage (IDW), Kriging and Spline [18]. We can accept or reject any of the technique depending upon the application for which we are applying it.…”
Section: Methodsmentioning
confidence: 99%
“…Subtropical regions are mostly hit by these events [5]. The crop phenology has put huge pressure on small farmers to grow healthy for obtaining sufficient grains which is enough to cater the weeds of increasing population [6]. Therefore, it is important to estimate the exact volume of net productions which make a decision maker to construct a concrete strategy for sustainable development [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…This urbanization growth has devasted urban balance and effected the sustainable development. The situation has become worse which lead to severe environmental issues and the climate change [2]. This climate change has affected the cropping system [3] glacial melting [4], severe flooding and droughts [5].…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have indicated a big difference in urban temperature in comparison to its outskirts [2,6,7,8]. Removal of vegetation for construction of buildings, malls and plazas, is considered the main cause of rise in urban temperatures [9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation